Probabilistic-based assessment of a masonry arch bridge considering inferential procedures - Moreira, Vicente Novo (2017)
Considering the safety assessment requirements of masonry arch bridges, different levels of reliability, based on uncertainty, may be distinguished, whose core objectives are to accurately analyse the ultimate load-carrying capacity and the serviceability structural response. Within this framework, a simplified full-probabilistic methodology for the safety assessment of existing masonry arch bridges is proposed, which combines both structural analysis and Bayesian inference procedures. The proposed framework aims to determine the ultimate load-carrying capacity (Ultimate Limit State) of masonry arch bridges, by using probabilistic procedures and Limit States principles. Geometric, material and load characterization, as well as inherent uncertainties will be also considered. In order to determine the ultimate loadcarrying capacity, a limit analysis approach, based on the mechanism method, will be employed. Due to the high computational costs required by a probabilistic safety assessment framework, a sensitivity analysis will then be introduced. The incorporation of new information from monitoring and/or testing will be performed by the application of Bayesian inference methodologies. Based on the information collected, two reliability indexes will be computed and compared, one with data collected from design documentation and literature and the other with data collected from testing, emphasizing the importance of testing and the advantages of Bayesian inference procedures. The probabilistic framework developed is tested and validated in a Portuguese railway masonry arch bridge from the 19th century.